Justification or Excuse? The Collision of Positive Duties in German Criminal Law. (June 2014) - Zimmermann, Till
Legal systems operating on the idea that not only positive acts, but also omissions can be criminally relevant may create 'legal traps' by demanding impossible behaviour where there is a collision of duties. This, however, cannot be the law. There must be a definite instruction to those confronted with conflicting duties. In German law, the solution of the collision of a positive with a negative duty is solved by applying the lesser-evil clause of s. 34 of the Criminal Code, granting a defence of necessity. The same idea is also applicable if two positive duties with different values collide. However, German law does not offer a solution if the positive duties are of equal value. While some argue that in such a case the person fulfilling one duty and thereby violating the other is merely excused, the analysis of the situation on the basis of the Rawlsian Theory of Justice leads to the conclusion that a justificatory defence should be offered to that person—even in cases of murder.